Acumulação de capacidades tecnlógicas e mecanismos subjacentes de aprendizagem relativos a gestão de processos: estudo de caso no setor de serviços bancários no Brasil - Rocha, Fernando Mendonça (2009)
This study examines the technological capability accumulation process for innovation and operation activities in process management and the underlying learning mechanisms in service fmns, particularly, in the bank industry, considering the specificities ofthe developing countries context. Over the last two decades, there have been numerous studies about technological capability accumulation and the underlying learning mechanisms. Although, are still scarce the empiric studies about the relationship of these both variables in services firms context, particularly, in the bank industry. The scarceness of the studies of this nature is strongly observed in Brazil. Therefore, intending to enlarge the understanding about the technological capability accumulation and the learning mechanisms in services fmns, this dissertation examines the managing processes technological function into a bank services firm, particularly, information and communication technology area from Bank ofBrazil, along the period of 1982 to 2008. Based on qualitative and quantitative first-hand empirical evidences, collected through an extensive field work, this dissertation found out the following results: 1. The ICT area of the firm has accumulated, to 2008 from 1982, technological capability in the process management through efforts in knowledge acquisition and conversion. Starting in the Basic Operational degree, being able just perform basic bank operations, it reached the Intermediate Innovative degree, being able to implement advanced changes in internaI managing processes. Besides, differences in the technological capability accumulation speed were found in this period and between the ICT internaI units, due to the efforts in processes management competence. Is relevant to say that the firm reached the 50 degree, in a six degree scale; 2. The learning processes have been essential sources to the technological capability accumulation in process management. The knowledge acquisition and conversion processes allowed the creation of a necessary base to assimilate more advanced and complex knowledge. Although the learning processes expressive importance, other internaI (organisational changes) and externaI (economic policies) factors also influenced the technological capability accumulation in process management. However, not only the quantity but mainly the behavior of the learning mechanisms was important during the period. The results observed in this study conclude that (i) technological capability accumulation path is an intentional, continuous and growing process deriving from the efforts and integrated investments in all of technologic capacity dimensions, (ii) the organisational learning mechanisms have influenced the technological capability accumulation, and (iH) the use of adapted models guarantee a faithful fmns behavior analyses. This study contributes to the comprehension of the technological capability accumulation complexity, vital factor in competitive differential of developing country fmns, and particularly to the bank industry, where competitiveness requires high quality internaI processes that results in operational efficiency and economic performance improvement. Besides, this study argues the organisational dimension importance as supporting the other dimensions, by managing internaI processes and organisational strategy. Moreover, this study also suggests to the Brazilian bank executives that an intentional creation of a continuous and cyclic process of learning mechanisms development, considering the keycharacteristics, assist the firm's technological capability accumulation path. Therefore, is important that these executives consider the investments in technological capability accumulation as a way to keep a competi tive and sustainable position on the market, adjusting the managerial to the organisational strategy.